Extended spectrum β-lactamase-producing Enterobacterales in live and dead birds from rural poultry farms and urban live bird markets of Bangladesh - Amin, Mohammed Badrul; Hoque, Kazi Injamamul; Sraboni, Ajrin Sultana; Bhuiyan, Omar Faruk; Happy, Tanjin Tamanna; Alam, Munirul; Mondal, Dinesh; Islam, Mohammad Aminul (Frontiers in Microbiology, 2025)
IntroductionPoultry raised with antibiotic prophylaxis are significant reservoirs of extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E). Improper disposal of poultry wastes is common in developing countries, increasing the risk of spreading ESBL-E. Previous studies largely focused on ESBL-producing E. coli in poultry, overlooking other Enterobacterales and dead birds.MethodsBetween December 2019 and June 2021, this study investigated 220 fecal samples collected from 55 freshly slaughtered and 55 dead birds in urban live bird markets and rural poultry farms in Bangladesh for detection and enumeration of ESBL-E.ResultsOverall 68% (n = 150) samples were positive for ESBL-E, with a significantly higher prevalence in urban live-bird markets (88%, n = 97) than rural poultry farms (48%, n = 53; p < 0.01, OR = 7.25, 95% CI: 3.77–14.71) and slightly higher in dead (n = 81, 74%) than live birds (n = 69, 63%). ESBL-producing E. coli was most common (66%, n = 146), followed by ESBL-producing Klebsiella pneumoniae (10%, n = 22), Raoultella terrigena (3%, n = 7) and Enterobacter spp. (3% n = 6). The abundance of ESBL-producing E. coli was significantly higher in urban live-bird markets than rural poultry farms (3.9 vs. 2.0 log10 CFU/g; p < 0.001, Cliff's Delta = 0.53, 95% CI: 0.40–0.65) and in dead than live birds (3.4 vs. 2.2 log10 CFU/g; p < 0.01, Cliff's Delta = 0.23, 95% CI: 0.08–0.38). The abundance of ESBL-producing K. pneumoniae, Enterobacter, and R. terrigena (1.6–1.8 log10 CFU/g) showed no significant difference between urban live-bird markets and rural poultry farms or between live and dead birds. A higher proportion of ESBL-E from urban live bird markets were resistant to 10 out of 11 antibiotic classes, compared to those from rural poultry farms (p < 0.05). Further, ESBL-E isolates from dead birds showed higher resistance to aminoglycosides, glycylcyclines, and penicillins+β-lactamase inhibitors than isolates from live birds (p < 0.05). Overall, 65% of isolates were resistant to penicillins, fluoroquinolones, and monobactams, while 2% were carbapenem-resistant. The prevalence of multi-drug resistant E. coli was higher in urban live bird markets (86%, n = 95) than rural poultry farms (45%, n = 49; p < 0.01). Among 181 ESBL-E, blaTEM (62%, n = 114) was the most prevalent, followed by blaCTX − M−group (17%, n = 32) and blaSHV (12%, n = 22).DiscussionThe widespread ESBL-E in poultry underscores the urgent need for improved biosecurity and waste management across the poultry supply chain.